“Bel Crouches; Nebo Travails” Reading Birth Imagery in Isaiah 46:1–4 - Schoening, Zachary J. (2023)
The traditional reading of Isa 46:1–4 understands the Babylonian gods as falling or toppling. Interpretation of the nature of their actions depends upon how one reads the verbiage applied to the deities, which hinges upon the translation of a series of either difficult or semantically diverse Hebrew terms. This essay analyzes these terms in light of comparative Semitic evidence. It also considers the passage in light of broader ancient Near Eastern ideological and mythological patterns. Finally, it explores some prominent motifs in the traditions of the Akītu festival, which constitutes the immediate frame of reference for the oracle’s imagery and against which Deutero-Isaiah was framing his rhetoric. Birth imagery, this essay contends, constitutes the primary rhetorical vehicle by which the prophet ridicules the Babylonian gods, portraying them as crouching in labor, and depicting them as inferior to Yahweh.